Nanoscale Surface Modifications of Orthopaedic Implants: State of the Art and Perspectives - Staruch, RMT (Open Orthop J, 2016)
BACKGROUND: Orthopaedic implants such as the total hip or total knee replacement are examples of surgical interventions with postoperative success rates of over 90% at 10 years. Implant failure is associated with wear particles and pain that requires surgical revision. Improving the implant - bone surface interface is a key area for biomaterial research for future clinical applications. Current implants utilise mechanical, chemical or physical methods for surface modification. METHODS: A review of all literature concerning the nanoscale surface modification of orthopaedic implant technology was conducted. RESULTS: The techniques and fabrication methods of nanoscale surface modifications are discussed in detail, including benefits and potential pitfalls. Future directions for nanoscale surface technology are explored. CONCLUSION: Future understanding of the role of mechanical cues and protein adsorption will enable greater flexibility in surface control. The aim of this review is to investigate and summarise the current concepts and future directions for controlling the implant nanosurface to improve interactions.